A novel method for measuring the structure sensitivity of molecular descriptors. (2nd June 2019) - Rakić, Marija; Furtula, Boris
Abstract : A response of a molecular descriptor on subtle structural changes is a parameter that shed light on its quality. Until now, there was a just one attempt to quantify this property. Here, a novel method for calculating this parameter, based on fingerprint molecular similarity, is given. Preliminary investigations show that this new method outperforms already existing one. In addition, some well‐established degree‐, distance‐, and eigenvalue‐based topological molecular descriptors are subjected to this test, using acyclic, unicyclic, bicyclic, and tricyclic decanes and sorted accordingly. Abstract : A response of a molecular descriptor on subtle structural changes is a parameter that shed light on its quality. A novel method for calculating this parameter, based on fingerprint molecular similarity, is given. Preliminary investigations show that this new method outperforms existing one. In addition, some well‐established degree‐, distance‐, and eigenvalue‐based topological molecular descriptors are subjected to this test, using acyclic, unicyclic, bicyclic, and tricyclic decanes and sorted accordingly.